2015
DOI: 10.31018/jans.v7i1.613
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening of white Jute (Corchorus capsularis L) against salinity stress

Abstract: Abstract:The environmental stress such as salinity of soil or water is serious threat for field crops in the world, especially in arid and semiarid regions. To study salinity stress on jute (Corchorus capsularis), an experiment was laid out in factorial randomized block design keeping nine capsularis varieties (JRC-698, JRC-321, JRC-517, JRC-7447, JBC-5, JRC-212, JRC-80, JRC-532 and UPC-94) as one factor and four levels of salt concentrations i.e. control (Distilled H 2 O), 100, 160, 240 and 300 mM NaCl with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…All genotypes recorded good results for shoot lengths under all salt solutions at 5 th day (Table 5). It was reported that for the shoot lengths, significant differences were found among the genotypes and salt treatments (38). Among six tossa jute genotypes, Acc.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All genotypes recorded good results for shoot lengths under all salt solutions at 5 th day (Table 5). It was reported that for the shoot lengths, significant differences were found among the genotypes and salt treatments (38). Among six tossa jute genotypes, Acc.…”
Section: Discussionmentioning
confidence: 96%
“…1407 gave relatively more root lengths at 14.0 dS m -1 . It was reported that significant differences were found for the root lengths among the genotypes and salt treatments (38).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seed germination and seedling growth are two crucial and vulnerable stages in the early life cycle of terrestrial angiosperms in regards to salinity stress. The relative reduction in seed germination and growth have earlier been used for assessing salt tolerance of jute in China (Ma et al, 2011) and for C. capsularis in India (Naik et al, 2015). Hence, the present investigation was undertaken to assess the tolerance of different high yielding white jute (C. capsularis) cultivars towards salinity sterss.…”
Section: Imposition Of Different Salinity Levelsmentioning
confidence: 97%
“…Various studies have investigated jute salt tolerance[ 13 ]. Naik et al [ 14 ] studied a few of Corchorus capsularis accessions under differential salt concentration, and the results showed that some varieties could be grown at 160 mM NaCl concentration. Taneenah et al studied the germination of Corchorus olitorius L underlying the Dead Sea water, sea water and water with differential NaCl concentration, and the results indicated that Corchorus olitorius L. showed high tolerance to Dead Sea water, sea water and NaCl up to 6‰[ 15 ].…”
Section: Introductionmentioning
confidence: 99%